PENGARUH KEPEMIMPINAN DAN KOMPETENSI TERHADAP PRESTASI KERJA KARYAWAN PADA YAYASAN PERGURUAN ISLAM AL-FAKHRIYYAH JAKARTA BARAT - Muhammad Nurdin; Lismiatun Lismiatun (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
The purpose of this study is to determine the influence of leadership and competence on employee work performance at the Al-Fakhriyyah Islamic College Foundation West Jakarta both partially and simultaneously. The method used in this study uses quantitative methods. The population in this study is 50 respondents with an associative approach, the sampling technique uses saturated sampling where all populations are used as samples in this study. Data analysis uses validity tests, realism tests, classical assumption tests, regression analysis, correlation coefficient analysis, determination coefficient analysis and hypothesis tests. Based on the results of the analysis, the regression equation value Y = Y = 1.716 + 0.404X1 + 0.556X2 was obtained. It can be interpreted that the value of the leadership regression coefficient is positive which is 0.584 and the value of the competency regression coefficient value is positive which is 0.871. The value of the simultaneous determination coefficient or its influence contribution of 0.866 or 86.6% indicates that Leadership and Work Achievement simultaneously contribute 86.6% to Work Performance, while the remaining 13.4% is influenced by other factors. In the results of the partial test (t-test) the influence of leadership on employee work performance showed a T-> Ttable value (4.986 > 2.011) with a significance value of 0.00 < 0.05 which means that leadership had an effect on employee work performance and the results of the partial test (t-test) of competence on employee work performance showed a T-> Ttable value (12.259 > 2.011) with a significance value of 0.00 < 0.05 whose competence had an effect on employee work performance. The results of the simultaneous test (Test F) showed the value of Fcal > Ftable (151.793 > 3.20) with a significant value of 0.000 < 0.05. This states that Ha3 is accepted, which means that leadership and competence (together) simultaneously affect the work performance of employees at the Alfakhriyyah Islamic Education Foundation West Jakarta.